Essays on Anatolian archaeology - Takahito, Japan, Prinz (Bulletin of the Middle Eastern Culture Center in Japan, 1993)
The Hittite dam of Karakuyu / Kutlu Emre -- A preliminary report on the third excavation at Kaman-Kalehöyük in Turkey (1988) / Masao Mori and Sachihiro Omura -- Ancient crop husbandry at Kaman-Kalehöyük / Mark Nesbitt -- Schutz-und Loyalitätsverpflichtungen in hethitischen Staatsverträgen / Albertine Hagenbuchner -- Ritual purity versus physical impurity in Hittite Anatolia / Ahmet Ünal -- Anatolian obsidian and the neolithic obsdian industries of North Syria / Yoshihiro Nishiaki -- Geo-archaeology in the northern Diyarbakir region / I. Caneva ... [et. al.]